2021
DOI: 10.1016/j.tafmec.2020.102854
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure-sensitive estimation of fatigue life using cyclic thermodynamic entropy as an index for metals

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 40 publications
4
23
0
Order By: Relevance
“…The two criteria for the determination of a proper α value 87 [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Microstructure‐sensitive Studies Using Statistical Representationmentioning
confidence: 99%
See 2 more Smart Citations
“…The two criteria for the determination of a proper α value 87 [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Microstructure‐sensitive Studies Using Statistical Representationmentioning
confidence: 99%
“… italicFFE=0tftrueγ0.25eṁitalicdt=0tftrueẇpTitalicdt, where ẇp is the rate of cyclic PSE, T is the steady‐state temperature from the surface of the material, and t f is the time to failure. Based on the earlier model of SEPSE and using the concept of FFE, Jirandehi and Khonsari 87 developed a microstructure‐sensitive and thermodynamically based framework to estimate fatigue life. Finite element simulations were adopted to discretize the thermodynamic laws of cyclic heat generation and to calculate the specimen surface temperature evolution.…”
Section: Microstructure‐sensitive Studies Using Statistical Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…46 In plastic deformations, the microstructure of material can be altered by the movement and reorientation of dislocations. 47 It was found that ultrasonic vibrations can remarkably enhance the dislocation density and the ratio of dislocation via grain refinement. Additionally, highly repeated contacts between the forming tool and the sheet metal will result in a facilitation of slip system's movement.…”
Section: Forming Limit Diagram (Fld)mentioning
confidence: 99%
“…In a tribo-system, degradation is accompanied by material removal [30][31][32][33][34][35]. The same physics is involved when one deals with a deterioration of performance in batteries during charging and discharging [36,37], loss of consistency in grease due to shearing action [38][39][40][41], and accumulation of damage in cyclic fatigue [42][43][44][45]. Therefore, it is hypothesized that the degradation can be characterized using the framework of irreversible thermodynamics.…”
Section: Introductionmentioning
confidence: 99%